Is Natural Law Timeless? - Jonathan Crowe (Bond Law Review)
Natural law theories hold that human action is oriented towards certain intrinsic goods and governed by practical principles accessible to us by virtue of our nature. These goods and principles make up the content of natural law. This essay argues that both the content of natural law and our understanding of its requirements evolve throughout human history. This represents a diachronic, rather than synchronic, understanding of natural law. This perspective is contrasted with the ‘new natural law theory’ of Germain Grisez and John Finnis, which depicts natural law as timeless and unchanging. Finnis seems to think that natural law does not change because it exists in the mind of God; however, a belief in God as the source of natural law is equally consistent with a diachronic perspective. I defend this view through reference to the writings of Thomas Aquinas and the structure of the biblical narrative.